First Amazonian species of Maracaynatum, with comments on the genus (Opiliones: Laniatores: Samoidae) - Colmenares, Pío A.; Tourinho, Ana Lúcia (Zootaxa, 2016)
Among Opiliones, the family Samoidae Sørensen, 1886 is a group of small Laniatores with a wide tropical distribution. Neotropical samoids are distributed mainly in the Caribbean subregion, with species recorded from insular localities and the Venezuelan coastal range. Previously, for continental South America only three genera and just a few specimens of unidentified Samoidae have been recorded from Brazil. In this paper we describe Maracaynatum isadorae sp. nov., the first record of the genus for Brazil and the first samoid described for the Amazon biome. We also provide an emended diagnosis for the genus and a map with its distribution.